2016
DOI: 10.1136/bjsports-2016-096075
|View full text |Cite
|
Sign up to set email alerts
|

Injury and illness in aquatic sport: how high is the risk? A comparison of results from three FINA World Championships

Abstract: Background Epidemiological information on injury/ illness is required to develop effective injury prevention strategies. Aim To assess the frequency and characteristics of injuries/illnesses (1) in the 4 weeks prior to and (2) during the Fédération Internationale de Natation (FINA) World Championships 2015 compared with 2013 and 2009. Method (1) Athletes answered a retrospective questionnaire, and (2) the medical staff reported injuries/ illnesses prospectively during the championships. Results (1) A quarter o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 75 publications
(88 citation statements)
references
References 29 publications
(52 reference statements)
3
66
0
Order By: Relevance
“…These preliminary results and their limitations support the value of running injury surveillance studies during international competitions (gymnastics continental and world championships) as is done with football,30 athletics28 and aquatics 29. In addition, pre-participation health questionnaires would be relevant for such injury surveillance29 35 since 10%–20% gymnasts present injury complaints at some time during a season,6 and this would provide vital information regarding any injuries occurring in the month preceding a championship and so better understand injury risks during international competitions.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…These preliminary results and their limitations support the value of running injury surveillance studies during international competitions (gymnastics continental and world championships) as is done with football,30 athletics28 and aquatics 29. In addition, pre-participation health questionnaires would be relevant for such injury surveillance29 35 since 10%–20% gymnasts present injury complaints at some time during a season,6 and this would provide vital information regarding any injuries occurring in the month preceding a championship and so better understand injury risks during international competitions.…”
Section: Discussionmentioning
confidence: 56%
“…In comparison to other individual sports and data available from international Championships using a similar injury surveillance system,24 the overall gymnastic injury incidence was also lower than those during athletics28 or aquatic29 championships.…”
Section: Discussionmentioning
confidence: 83%
“…A retrospective survey at the 2013 WCh demonstrated that 41.9% of all responding water polo players had a physical complaint during the 4-week study period preceding the WCh; 43.8% reported that their training was affected, and only 31.3% were symptom free at the commencement of the WCh 14. This finding was confirmed at the 2015 WCh, which found that 27% of all responding water polo players had a physical complaint during the 4 weeks prior to the WCh; 68.1% of all aquatic athlete physical complaints during the study period were reported to have been caused by overuse injuries and 69.6% were still present at the beginning of the WCh 15. Thus, water polo athletes train and compete with injuries 14 15 35.…”
Section: Discussionmentioning
confidence: 83%
“…The present study analysed all water polo injuries reported during four Summer OG (2004,16 2008,17 2012,18 201619 and four FINA WCh (2009,13 2013,14 2015,15 2017). The study design, study implementation, injury definition, data collection and analysis procedures were similar at all tournaments, and have previously been described in detail 13–19…”
Section: Methodsmentioning
confidence: 99%
“…Other important elite athlete health-related topics that have been identified in the scientific literature as important parameters in elite athlete health that are identified in this study as being of low priority for IFs include ‘ eating disorders ’13, ‘ protection from harassment and abuse ’14 and ‘ Relative Energy Deficiency in Sport (RED-S) ’15. Furthermore, although 24 IFs reported that they undertook programmes in ‘ injury surveillance during IF championships ’, only six IFs have published their results (IAAF,16 FINA,17 FIFA,18 WR,19 International Handball Federation,20 Federation International de Volleyball21 and despite 19 IFs reporting ‘ pre-participation medical examinations ’, only one IF published their activity (FIFA) 22…”
Section: Discussionmentioning
confidence: 99%